Assessment of technological level of repair enterprises - Didur, V.; Petrychenko, I.; Viunyk, Olha; В’юник, Ольга Володимирівна (Запоріжжя : 2023, 2023)
EN: The enterprise for the repair of machine and tractor fleet is a system of technological means of production that works in a dynamic environment with changing conditions and types of products - repair of mobile machines and their elements in field and stationary conditions, equipment of livestock farms, restoration and manufacture of parts, provision of other services of a technical and technological nature. This achieves the extension of the life cycle of machines and their elements by restoring operability after failure. It is known that there are no exact rules that allow building a system of technological means of service on the basis of inviolable laws and rules. Therefore, the search for an adequate assessment of the technological level of a repair enterprise is carried out with the help of informal considerations, analogies, intuition, experience.
Keywords: aggregating; formalizing and clarifying the activities of the repair enterprise; rocess of improving the enterprise's activities; applying the aggregate repair method